Analisis Aliran Daya Pada PLTGU Blok 1 PT. PJB Unit Pembangkitan Gresik - Niken Dwi Apriliani; Titiek Suheta; Affan Bachri (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2020)
The purpose of research was to determine the condition of the power flow (active and reactive power), the voltage of each channel (bus) under normal operating conditions, and the power loss (losses) of each bus at the Block 1 PLTGU PT. PJB Gresik Generating Unit. The method used to analyze the power flow is Forward Backward Sweep by forming a BIBC and BCBV matrix, where the results of the analysis will be compared with the results of the simulation. From the results of comparison of calculations and simulation of power flow obtained active power (P) of 1% and reactive power (Q) of 1.76%. The biggest voltage drop on bus 5 is 7% and is a critical bus condition, because the voltage drop is ± 5% of the nominal voltage. The largest value of power losses is on bus 4 with an active power of 1.14% and a reactive power of 0.5%. Whereas for other bus conditions such as bus 2 including marginal bus conditions, bus 3 with bus 6 are critical bus conditions, because each bus has a voltage drop of ± 5% of nominal voltage.